2019
DOI: 10.13005/ojc/350166
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Screening and Antidiabetic Activity of N-Hexane, Ethyl Acetate and Water Extract from Durian Leaves (Durio Zibethinus L.)

Abstract: The leaf of Durian (Durio zibenthinus L.) contain flavonoids and steroids in ethanol extract. Natural flavonoids have an important role in the prevention of diabetes and its complications and are able to provide good effects in the fight against diabetes mellitus, either through the ability to reduce glucose absorption and improve glucose tolerance. The purpose of this research is to know the activity of antidiabetic extract of n-hexane, ethyl acetate and water from durian leaf ethanol extract. The results of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 7 publications
(7 reference statements)
0
2
0
1
Order By: Relevance
“…Into one tube, 1 mL of the 1 mg/mL test solution was transferred and serially diluted, ranging from 0.05 mg/mL to 0.75 mg/mL. After that, 0.1 mL of inoculum was inoculated, and the tubes were then cultured for 24…”
Section: Minimum Inhibitory Concentration Assay (Mic)mentioning
confidence: 99%
See 1 more Smart Citation
“…Into one tube, 1 mL of the 1 mg/mL test solution was transferred and serially diluted, ranging from 0.05 mg/mL to 0.75 mg/mL. After that, 0.1 mL of inoculum was inoculated, and the tubes were then cultured for 24…”
Section: Minimum Inhibitory Concentration Assay (Mic)mentioning
confidence: 99%
“…(Family Bombacaceae) is a type of tropical fruit plant called durian that has been widely cultivated in Malaysia and other Southeast Asian countries. Researchers have reported that antioxidant, anticancer, antidiabetic, antilipoxygenase, anti-heart disease, and anti-obesity properties can be attributed to durian [12,13]. One of the purported medicinal and therapeutic benefits of durian fruit is its capacity to fortify the immune system.…”
Section: Introductionmentioning
confidence: 99%
“…Senyawa fenolik juga diduga memiliki aktivitas sebagai antihiperurisemia karena mampu menghambat kerja dari enzim xantin oksidase. 8,9,10 Xantin oksidase merupakan enzim kunci pada manusia, terutama pada metabolisme purin dengan bertindak sebagai katalis reaksi hidroksilasi oksidatif hipoxantin menjadi xantin dan hasil selanjutnya adalah pembentukan asam urat. 11 Jalur ini merupakan jalur degradasi purin dengan penurunan O2 di pusat flavin dan menghasilkan Reactive Oxygen Species (ROS), baik radikal anion superoksida atau hidrogen peroksida.…”
Section: Pendahuluanunclassified
“…The yield of the extracts and debt to equity ration (DER) obtained from ethanol extract listed in Table-1. Screening of extract ethanol from durian leaf such as steroids/terpenoids, flavonoids, an glycosides 7 . The result of extraction and partition for samples showed that the water extract had the highest yield (7.04%) among other extracts (0.2 -0.8%).…”
Section: Extraction and Partitionmentioning
confidence: 99%